Technology and Theology: A Qualitative Study of Social Media Use for Religious Education - Gregory C. Carrow-Boyd (Adult Education Research Conference, 2013)
This study examines the experiences of Unitarian Universalist religious educators learning to use social media for religious education purposes. Initial findings indicate that this learning impacts overall social media use.